Launching a program for investment partnerships - Matthew Stephenson (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
There are growing win-win opportunities for partnership between investment-related institutions in different economies, both for knowledge sharing and to facilitate two-way investment. This Perspective proposes concrete ways to launch a program to grow such partnerships while providing suggestions for specific joint activities.
Keywords: 330